Applied research for growth, innovation and sustainable impact - Patrick, Harold Andrew; Krishnamoorthy, Ravichandran, 1969- (Routledge, 2026)
Innovative Management Science Practices: Bridging Theory and Applied Research delves into the dynamic interplay between theoretical frameworks and practical applications in management. This insightful anthology compiles groundbreaking research and detailed case studies that highlight innovative practices across various domains, including organizational governance, strategic decision-making, marketing strategies, financial management, human resource development, and the integration of advanced technology
Keywords: Business enterprises -- Technological innovations.; Economic development.; Sustainability.; elektronické knihy; electronic books